I.i.11.c Minutes - Labour Party (Ireland) (1980)
Minutes of the Administrative Council which took place on principally concerning: party programme; dates for Party conference 1980; establishment of a fundraising committee; ‘head office newsletter’; proposed establishment of Labour Student’s organisation; party finances; the raising of an interest free loan of three million Belgian Francs against Party Headquarters, 16 Gardiner Place, Dublin 1, County Dublin; financial contribution of Labour Party Members of the European Parliament (MEP’s); letting of the basement of Party Headquarters, 16 Gardiner Place, Dublin 1, County Dublin to Alcoholics Anonymous (AA); staff salaries and pensions; special constituency council meetings regarding the Party finances; budget deficit; motion regarding participation in May Day activities; establishment of policy sub-committees; Zimbabwe elections; fraternal relations with Zimbabwe African National Union and Patriotic Front (ZANU-PF) parities in Zimbabwe; taxation of the financial sector; and the Raidió Teilifís Éireann (RTE) programme ‘Strumpet City’. Minutes signed by Michael D[aniel] Higgins, Party Chair. Also includes: administrative committee report; Parliamentary Labour Party report; report of the General Secretary; finance committee report; organisation committee report; memorandum entitled ‘Pilot Scheme on Organisational Development’ prepared by Senator Jack Harte, Honorary National Organiser; policy committee report; national youth committee report; report of the International Secretary; and list of correspondence received. (46 pp)